2019
DOI: 10.5114/wiitm.2019.90565
|View full text |Cite
|
Sign up to set email alerts
|

Does sleep deprivation alter virtual reality-based robotic surgical skills?

Abstract: Introduction: Robotic surgery is widely used in many surgical specialities, and there has been no study to assess the impact of sleep deprivation on the complex environment of robotic surgery. Aim: To compare specific metrics of selected robotic simulator exercises on sleep-deprived and non-sleep-deprived surgical residents. Material and methods: We enrolled 20 volunteers, residents in surgery, evaluated before and after an 18-hour overnight shift, regarding their results on virtual robotic surgery simulator-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As aforementioned, the data concerning a decrease in surgical skills in sleep deprived residents are conflicting. It is also of note that all of the papers citing a decline in surgical skills when sleep deprived measured skill level using various simulated tasks [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]24,[58][59][60][61][62][63][64][65][66][67][68]. These findings may not be directly transferrable to actual everyday surgeries, as surgeons are rarely operating alone in these situations, so mistakes may be caught or corrected by colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, the data concerning a decrease in surgical skills in sleep deprived residents are conflicting. It is also of note that all of the papers citing a decline in surgical skills when sleep deprived measured skill level using various simulated tasks [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]24,[58][59][60][61][62][63][64][65][66][67][68]. These findings may not be directly transferrable to actual everyday surgeries, as surgeons are rarely operating alone in these situations, so mistakes may be caught or corrected by colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, the available literature evaluating surgical performance when sleep deprived is very conflicting. Many studies show a decrease in performance when surgeons are asked to perform various simulated surgical tasks post call [6][7][8][9][10][11][12][13][14][15][16]. A systematic review of the effects of acute sleep deprivation on surgeons found that of the 21 papers analyzed, 12 showed a negative effect on surgical skills [17].…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the role of working memory. The working memory was described in sleep-deprivation studies as keeping task-relevant information for a few seconds in order to be used for routine ongoing activities, and it has been proved that it is not always affected by sleep deprivation/ tiredness [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…During the university classes, medical students have practically no contact with the laparoscope, apart from observing the procedures carried out by older, experienced surgeons. Medical students and young adepts of orthopaedics and surgery should have constant contact with laparoscopic trainers [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Cumpanas et al [ 21 ] examined how sleep deprivation influenced performance on the robotic virtual reality simulator. In their research sleep deprivation does not influence the time of performance on easier tasks but influences time of performing more difficult tasks.…”
Section: Discussionmentioning
confidence: 99%